Cardiovascular Health in Children and Adolescents With Congenital Adrenal Hyperplasia Due to 21-Hydroxilase Deficiency - Improda, Nicola; Barbieri, Flavia; Ciccarelli, Gian Paolo; Capalbo, Donatella; Salerno, Mariacarolina (Frontiers in Endocrinology, 2019)
Increasing evidence indicates that adults with Congenital Adrenal Hyperplasia (CAH) may have a cluster of cardiovascular (CV) risk factors. In addition, ongoing research has highlighted that children and adolescents with CAH are also prone to developing unfavorable metabolic changes, such as obesity, hypertension, insulin resistance, and increased intima-media thickness, which places them at a higher risk of developing CV disease in adulthood. Moreover, CAH adolescents may exhibit subclinical left ventricular diastolic dysfunction and impaired exercise performance, with possible negative consequences on their quality of life. The therapeutic management of patients with CAH remains a challenge and current treatment regimens do not always allow optimal biochemical control. Indeed, overexposure to glucocorticoids and mineralocorticoids, as well as to androgen excess, may contribute to the development of unfavorable metabolic and CV abnormalities. Long-term prospective studies on large cohorts of patients will help to clarify the pathophysiology of metabolic alterations associated with CAH. Meanwhile, further efforts should be made to optimize treatment and identify new therapeutic approaches to prevent metabolic derangement and improve long-term health outcomes of CAH patients.